Development of etnosains baset LKPD integrated thingking critikal student - Tryo Balun Prima (Department of Science Education, 2022)
This type of research is Research and Development (R & D) which aims to determine the development process and the validity of LKPD, the validity of LKPD based on Integrated Ethnosaians with Critical Thinking of Students. The research location is at SMPN 29 Padang class VII odd semester on object classification material. The LKPD components developed in this study were the LKPD content. The LKPD development model being developed refers to the 4-D model which has been modified into 3-D, namely defining, designing, and developing. The research instrument used was the validation sheet used to obtain data on the level of validity of student worksheet based on Etonoscience Integrated Critical Thinking. The data obtained were analyzed descriptively. The results of descriptive descriptive analysis related to using LKPD validation analysis obtained a validity level with an average value of 3.13 can be said to be valid.